Deepening our collective understanding of decolonising education: A commentary on Simaan's learning activity based on a Global South community. Issue 3 (2nd July 2020) - Gibson, Chontel; Farias, Lisette
ABSTRACT: This invited commentary responds to Simaan's (2020 ) article, which highlights a decolonising learning activity centred on a study from a Global South community. It extends the theoretical discussion in Simaan's article, highlighting how Santos' intercultural translation and Paulo Freire's work can deepen a decolonised approach to occupations and teaching occupations. This commentary raises concerns that teaching decolonised pedagogies in a predominately Western curriculum and discipline can be risky for both teachers and students. Furthermore, it is argued that decolonising pedagogies should include anti-racist strategies embedded in curricula that are decolonised.